ENTREPRENEURIAL ORIENTATION MODEL IN CREATING PRODUCT QUALITY TO INCREASE COMPETITIVE ADVANTAGE - Sungkawati, Endang; Dwi Hernanik, Nova; Prawoto, Budi (Penerbit Lafadz Jaya, 2023)
This study aims to prove how product quality can mediate entrepreneurial orientation in increasing a firm's competitive advantage. This research was conducted in a tourism village business unit located in the East Java region, with a sample of 115 respondents. This study used questionnaires for data collection and data analysis using path analysis. The study results stated that entrepreneurial orientation can create quality products but cannot increase competitive advantage. While quality products grow competitive advantage, product quality can mediate entrepreneurial orientation in improving a firm's competitive advantage.